Frailty decreases physical health domain of quality of life in nursing home elderly - Handajani, Yvonne Suzy; Widjaja, Nelly Tina; Turana, Yuda (Faculty of Medicine, Trisakti University, 2015)
BACKGROUND Approximately 10-27% of the population aged >65 years suffers from frailty. The percentage increases with age so that the prevalence of frailty in the population aged >85 years reaches 45%. The objective of this study was to determine the relationship betweenÂ Â frailty and quality of life (QOL) in nursing home elderly. METHODS This was a cross-sectional study of 138 subjects aged >60 years who were recruited from 4 nursing homes in West Jakarta. Participants with frailty status were evaluated by the Survey of Health, Ageing and Retirement in Europe (SHARE) instrument and QOL was evaluated by the WHOQOL-BREF questionnaire. One-way ANOVA and chi-square tests were used to find relations between the frailty syndrome and QOL. RESULTSThe percentages of respondents with pre-frail, frail, and non-frail status were 30.4%, 52.2%, and 17.4%, respectively. A decline in QOL scores of pre-frail and frail respondents was found for almost all QOL domains (physical, psychological and environment domains), except social relationships. The subdomains most influenced were â€œenergy and fatigueâ€ in the physical health domain, â€œthinking, learning, memory and concentrationâ€ in psychological health, and â€œopportunities for acquiring new information and skillsâ€ in the environment domain.CONCLUSIONS More than half of the nursing home elderly were frail and one-third were pre-frail. The main factor of frailty was weakness. The frailty syndrome in the elderly has a negative impact on QOL, especially in the physical health, psychological and environment domains in nursing home elderly.